(untitled) (Sains Humanika, 2018)
This descriptive study was carried out through a questionnaire on ten schools in the Kuala Kangsar Zone of Perak to observe the clinical supervision of principals. The main purpose is to identify teachers’ perceptions of clinical supervision that was carried out by the principals and to see the effectiveness of supervision towards the quality of teaching in schools. A total of 175 sets of questionnaires were distributed to teachers in eight selected schools. Pilot study was conducted to determine the reliability of instrument of the study. The data were collected quantitatively and analyzed using the Statistical Package For Social Sciences (SPSS) version 20.0. The Pearson Correlation Test was used to test the hypothesis of this study. In addition, mean, frequency, and percentage are also used in analyzing data. The findings revealed that teachers’ perceptions of clinical supervision conducted by principals were high. The efficacy of clinical supervision in study schools was also high. The three main phases of the clinical supervisory approach are clearly carried out by the principles as a supervisor. From the analysis of the correlation test, there is a significant correlation between the perceptions of the teachers towards the quality of teaching. At the end of the study, recommendations on the implementation of clinical supervisory exercises at the school were outlined, along with suggestion of future research.